Perlindungan Hukum terhadap Penyelenggara Social-Commerce atas Larangan Transaksi pada Platform Social-Commerce Berdasarkan Hukum Positif Indonesia - Hartyanto, Satrio Bagus; Rosadi, Sinta Dewi; Ramli, Tasya Safiranita (Jurnal Pendidikan Indonesia, 2025)
The development of social commerce in Indonesia faces legal challenges due to the transaction ban stipulated in Permendag 31/2023. This regulation prohibits social commerce platforms from facilitating direct transactions within their systems, leading to the closure of TikTok Shop in October 2023. However, TikTok Shop resumed operations after acquiring Tokopedia, sparking debates over regulatory compliance and legal certainty for business actors. This study employs a normative juridical method to analyze the legal protection for social commerce providers regarding the transaction ban. The findings indicate that this policy impacts micro, small, and medium enterprises (MSMEs) and creates legal uncertainty. Moreover, the ban contradicts the partnership principle in trade law and Mochtar Kusumaatmadja’s legal development theory, which emphasizes that law should drive economic growth. This study recommends regulatory adjustments to align with technological advancements while ensuring protection for business actors and consumers in the digital ecosystem